Evaluation of the Antioxidant and Antihyperglycemic Activity: A Comparative Study of Shallot (Allium ascalonicum L.) Peel and Bulb Ethanol Extracts - Efendi, M. Rifqi; Dwiyanti, Fadila; Oktavionita; Rusdi, Mesa Sukmadani; Armenia (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2025)
Diabetes Mellitus (DM), known as hyperglycemia, is a growing global health concern. Among medicinal plants explored for their potential in diabetes treatment, Allium ascalonicum L. (shallot) has gained significant attention. This study investigated the effectiveness of shallot peel and bulb extracts as antihyperglycemia activity in alloxan-induced diabetic rats. The total phenolic and flavonoid contents, and antioxidant activity of the extracts were also assessed. Shallot peel and bulb were extracted using ethanol-based maceration, followed by total phenolic content (TPC) and total flavonoid content (TFC) evaluation using the Folin–Ciocalteu and aluminium chloride methods, respectively. Antioxidant activity was determined by the DPPH radical scavenging assay. Diabetic rats were divided into four groups: negative control, positive control (metformin), and two treatment groups receiving 150 mg/kg of shallot peel or bulb extract for 10 days. Parameters such as fasting blood glucose, body weight, urine volume, food, and water intake were also monitored. The results showed significantly higher TPC in peel (347.6±1.7 mg GAE/g) than bulb (78.7±1.90 mg GAE/g), with p = 0.001 (p < 0.05). Peel also had higher TFC (56.60±1.63 mg QE/g vs. 30.4±0.81 mg QE/g in bulb), with p = 0.001 (p < 0.05) and superior DPPH scavenging capacity (IC50 of 124.814 μg/mL compared to 1,712 μg/mL in bulb extract). Both extracts significantly reduced fasting blood glucose levels, with the peel extract being the most effective in glycemic control, while the bulb extract showed greater improvement in diabetic symptoms. These findings suggest that ethanol extracts of shallot peels and bulbs are promising natural antioxidants with antihyperglycemic properties. Their phenolic and flavonoid richness supports their potential in diabetes management.